2022
DOI: 10.3390/ijerph19031575
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension in Morbid Obesity after Bariatric Surgery: Five Years of Follow-Up, a Before-And-After Study

Abstract: Background: Arterial hypertension (HTN) is common among morbidly obese patients undergoing bariatric surgery. The aim of this study is to analyse the prevalence and evolution of HTN and weight loss in patients suffering from morbid obesity before and after bariatric surgery, during a follow-up period of five years. Methods: A before-and-after study was carried out on severely obese patients undergoing Laparoscopic Roux-En-Y Gastric Bypass (LRYGB). Criteria for HTN diagnosis were current treatment with antihype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The dependence between BMI with a significant number of indicators and indices on it was proved. The results of our study confirmed the highly correlated positive dependence of BMI and WC, HC, calculated indices of abdominal obesity BSA, WHR, ConI, ABSI, AVI in patients with obesity of the first and second degree, which coincides with the data of M. Gažarová et al Blood pressure levels and lipid metabolism indicators correlated with BMI, which confirms the data K. Foti et al [26], W. Zhang [27], A. Arias et al [28], who noted the presence of such connections in their research. Although this dependence is controversial in the general population, given the research by D. Højland Ipsen et al [29], there is the presence of lipid metabolism disorders in patients with normal BMI as well.…”
Section: Discussionsupporting
confidence: 91%
“…The dependence between BMI with a significant number of indicators and indices on it was proved. The results of our study confirmed the highly correlated positive dependence of BMI and WC, HC, calculated indices of abdominal obesity BSA, WHR, ConI, ABSI, AVI in patients with obesity of the first and second degree, which coincides with the data of M. Gažarová et al Blood pressure levels and lipid metabolism indicators correlated with BMI, which confirms the data K. Foti et al [26], W. Zhang [27], A. Arias et al [28], who noted the presence of such connections in their research. Although this dependence is controversial in the general population, given the research by D. Højland Ipsen et al [29], there is the presence of lipid metabolism disorders in patients with normal BMI as well.…”
Section: Discussionsupporting
confidence: 91%
“…The molecular mechanism of hypertension remission after gastrectomy for gastric cancer patients is unclear, but it might be related to bariatric surgery for obese patients[ 29 , 30 ]. There were many possible molecular mechanisms of hypertension remission for obese patients after bariatric surgery: elevated activation of the renin–angiotensin–aldosterone system in obese patients might normalize after surgery[ 31 ] and the improvement of gastrointestinal gut hormone levels and insulin resistance after surgery[ 32 ], a possible effect of these gut hormones on the sympathetic nervous system[ 33 ], adipokines and other inflammatory cytokines would lead to hypertension recovery[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several comorbidities have been studied in relationship with severe COVID-19, and it was observed than 25% of hospitalized patients and approximately three quarters of ICU patients with SARS-CoV-2 had at least one comorbid condition [ 22 , 23 ]. Comorbidities such as hypertension, cardiovascular disease, and diabetes mellitus were the most common and often mentioned in reports around the world [ 24 , 25 ], and all are known to be connected with obesity, and indeed, obesity is increasingly recognized as both a comorbidity and a risk factor [ 26 , 27 ]. Obesity prevalence rises with age in both men and women, having significant consequences for global health, since excess weight, as measured by an elevated body mass index (BMI), affects a large proportion of the world’s population, with almost 40% being overweight, and more than 10% obese [ 28 ].…”
Section: Introductionmentioning
confidence: 99%